Assessment of Malaysian Cornsilk Bioactive Compounds and Its Cytotoxicity test on Brine Shrimp (Artemia salina) - Wan Rosli, W. I.; Mat Ali, Solihah (School of Health Sciences, Universiti Sains Malaysia, 2016)
Cornsilk contains various beneficial phytochemical compounds. There are claims that cornsilk exhibits various biological activities in vivo. The aim of the present study was to determine the cornsilk bioactive compounds and the cytotoxicity effect of cornsilk extract on brine shrimp. Cornsilk was extracted using different solvents with single extraction procedures. All phytochemical compounds samples were identified via GC-MS equipment. The brine shrimp toxicity test was observed to obtain LC50 value for both extracts. Eleven compounds were identified in the aqueous extract of cornsilk (AEC) while methanolic extract of cornsilk (MEC) contained 4 compounds. These compounds consist of cyclopentane-ethyl, 2-methylheptane, furfural, furfuryl alcohol, furfuryl-5-methyl, 1-naphtol, lactone-G, cis-2-pentenal, pyranone, hydroxymethyl furfural and palmitic acid. There was only 1 similar compound found in both extracts which was the hydroxymethyl furfural. Cytotoxicity test showed that cornsilk is non toxic. The LC50 values found in AEC and MEC were 3151.34 and 1350.65, respectively. Our result found that cornsilk contained various bioactive compounds which positively supported most of the therapeutic activity claimed. In brief, the cytotoxicity test shows that cornsilk is non toxic for human consumption due to its high LC50 value.